VITAMIN D3 DEFICIENCY AND THE EFFECTIVENESS OF SUBLINGUAL SUPPLEMENTATION – A REVIEW OF CLINICAL STUDIES - Illia Koval; Wiktor Kubik; Bartłomiej Czarnecki; Jan Nowak; Bartosz Zwoliński; Kacper Sukiennicki; Wirginia Bertman; Natalia Kołdej; Zuzanna Kępczyńska; Katarzyna Szewczyk; Kamil Borysewicz; Klaudia Romejko; et al. (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and Aim: Vitamin D3 plays a crucial role in numerous metabolic processes, and its deficiency remains a global public health concern, particularly among children, the elderly, pregnant women, and individuals with obesity or chronic diseases. Limited sunlight exposure and inadequate dietary intake contribute to this deficiency. Traditional oral forms of supplementation (capsules, drops) may lead to variable absorption and reduced adherence, especially in populations with swallowing difficulties. The aim of this review was to assess the effectiveness of sublingual vitamin D3 supplementation compared with conventional oral formulations.Materials and Methods: A review of randomized and controlled clinical trials published between 2015 and 2021 was conducted. Studies comparing sublingual (buccal) spray with oral capsules or drops in adults and children were analyzed for serum 25-hydroxyvitamin D [25(OH)D] levels, bioavailability, and patient acceptability.Results: Clinical evidence indicates that sublingual vitamin D3 spray demonstrates comparable or greater efficacy in increasing serum 25(OH)D concentrations relative to oral capsules. In adults, sublingual administration provided faster absorption and improved bioavailability, especially in patients with intestinal malabsorption. In pediatric populations, sprays were equally effective as oral drops and showed higher acceptance due to ease of use. Improved compliance was observed across studies.Conclusions: Sublingual vitamin D3 supplementation is an effective and well-tolerated alternative to traditional oral administration, particularly beneficial for individuals with absorption disorders or swallowing difficulties. Further research is needed to optimize dosage and duration in different risk groups.